PENGARUH PERSONAL SELLING DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN POLIS ASURANSI PT.QBE GENERAL INSURANCE INDONESIA CABANG MAKASSAR - Rani Rifani Arifuddin; Abdul Rahman Kadir; Nuraeni Kadir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to analyze the influence of personal selling and digital marketing to purchase decision of insurance policy in PT. QBE General Insurance Indonesia, Makassar Branch. The data of this research from questionnaire result to 87 customer of PT. QBE, Makassar Branch. Regarding the purchase decision of the insurance policy by using multiple regression analysis system, the research show that personal selling and digital marketing have partial effect to purchase decision with the result show that ttest of personal selling 4,206>ttabel 3,101 and ttest of digital marketing variable 4,076 > ttabel 3,101. Result from this research also show that personal selling and digital marketing have simultaneous positive effect for purchase decision of policy insurance 87.7% and 12.2% explained form other variable outside this research.